Reconfiguration of Functional Dynamics in Cortico-Thalamo-Cerebellar Circuit in Schizophrenia Following High-Frequency Repeated Transcranial Magnetic Stimulation - Huang, Huan; Zhang, Bei; Mi, Li; Liu, Meiqing; Chang, Xin; Luo, Yuling; Li, Cheng; He, Hui; Zhou, Jingyu; Yang, Ruikun; Li, Hechun; Jiang, Sisi; et al. (Frontiers in Human Neuroscience, 2022)
Schizophrenia is a serious mental illness characterized by disconnection between brain regions. Transcranial magnetic stimulation is a non-invasive brain intervention technique that can be used as a new and safe treatment option for schizophrenia patients with drug-refractory. However, the therapeutic effects of transcranial magnetic stimulation remain unclear. A longitudinal design was adopted to investigate the alteration of FC dynamics using a dynamic functional connectivity (dFC) approach in schizophrenia patients following high-frequency repeated transcranial magnetic stimulation (rTMS) with target at left dorsolateral prefrontal cortex (DLPFC). Two groups of schizophrenia inpatients were recruited. One group received a four-week high-frequency rTMS together with antipsychotic drugs (TSZ, n = 27); the other group only received antipsychotic drugs (DSZ, n = 26). Resting state functional magnetic resonance imaging (fMRI) and psychiatric symptoms were obtained from the schizophrenia patients twice at baseline (t1) and after 4-week treatment (t2). The dynamics was evaluated using voxel- and region-wised FC temporal variability resulted from fMRI data. The pattern classification technique was used to verify the clinical application value of FC temporal variability. For the voxel-wised FC temporary variability, the repeated measures ANCOVA analysis showed significant treatment × time interaction effects on the FC temporary variability between the left DLPFC and several regions including thalamus, cerebellum, precuneus, and precentral gyrus, which are mainly located within the cortico-thalamo-cerebellar circuit (CTCC). For the ROI-wised FC temporary variability, our results found significant interaction effect on the FC among CTCC. rTMS intervention leaded to the reduced FC temporary variability. In addition, higher alteration of FC temporal variability between left DLPFC and right posterior parietal thalamus predicted higher remission ratio of negative symptom scores, indicating that the decrease of FC temporal variability between brain regions was associated with the remission of schizophrenia severity. These findings confirm the potential relationship between the reduction in whole brain functional dynamics induced by high-frequency rTMS and the improvement in psychiatric scores, suggesting that high-frequency rTMS affects psychiatric symptoms by coordinating the heterogeneity of activity between brain regions.